Integrasi Quick Response Dinamis dan Algoritma Geofencing pada Sistem Presensi Terpadu untuk Validasi Kehadiran - Tiara Imanuela Putri Tehamen; Lisye Gladis Mengi; Tanjung Maharani Teksar; Herry Setiawan Langi; Steven Johny Runtuwene (Journal of Information System Research (JOSH), 2026)
The integrity of student attendance data in educational settings often faces serious challenges, particularly related to manipulation loopholes such as the use of absenteeism and inconsistencies in attendance locations. In a case study at SMK Kristen Imanuel Laikit, the existing attendance recording method was not fully capable of simultaneously validating location points and identities, potentially triggering administrative fraud. Responding to these problems, this study aims to propose the integration of geofencing and dynamic quick response (QR) algorithms into an integrated attendance system to minimize attendance validation manipulation. Technically, the system generates dynamic QR tokens whose patterns are continuously regenerated every few seconds through a time-based token generation mechanism and a random string combination. This automatic update is strictly designed to prevent reuse of authentication tokens, including the practice of sharing QR code screenshots with other students. Meanwhile, the geofencing mechanism is implemented through the Haversine algorithm calculation to validate the user's device position based on the school's specified radius tolerance limit. This system also integrates an autonomous discipline management mechanism that processes student attendance status based on the timeliness of attendance. Based on software testing results, the system is capable of precisely executing authentication, location validation, QR token synchronization, access rights control, and invalid attendance rejection in an integrated manner. This research contributes to the development of a secure attendance system that is free from location manipulation and QR code duplication. Furthermore, this system is designed to independently manage student discipline to create transparent and accountable academic governance.